Data from: Temporal specificity of the initial adaptive response in motor adaptation - Joiner, Wilsaan M.; Sing, Gary C.; Smith, Maurice A. (Dryad, 2018)
Repeated exposure to a novel physical environment eventually leads to a
mature adaptive response whereby feedforward changes in motor output
mirror both the amplitude and temporal structure of the environmental
perturbations. However, adaptive responses at the earliest stages of
learning have been found to be not only smaller, but systematically less
specific in their temporal structure compared to later stages of learning.
This observation has spawned a lively debate as to whether the temporal
structure of the initial adaptive response is, in fact, stereotyped and
non-specific. To settle this debate, we directly measured the adaptive
responses to velocity-dependent and position-dependent force-field
perturbations (vFFs and pFFs) at the earliest possible stage of motor
learning in humans–after just a single-movement exposure. In line with
previous work, we found these earliest stage adaptive responses to be more
similar than the perturbations that induced them. However, the
single-trial adaptive responses for vFF and pFF perturbations were clearly
distinct, and the disparity between them reflected the difference between
the temporal structure of the perturbations that drove them. Critically,
we observed these differences between single-trial adaptive responses when
vFF and pFF perturbations were randomly intermingled from one trial to the
next within the same block, indicating perturbation response specificity
at the single trial level. These findings demonstrate that the initial
adaptive responses to physical perturbations are not stereotyped. Instead,
the neural plasticity in sensorimotor areas is sensitive to the temporal
structure of a movement perturbation even at the earliest stage in
learning. This insight has direct implications for the development of
computational models of early-stage motor adaptation and the evolution of
this adaptive response with continued training.
Motion and force dataMATLAB data file (.MAT) with experimental data for
Joiner et al 2017joineretal2017data.mat